Physical chemistry water variation of the swamp El Eneal, Sanguaré natural reserve municipality of San Onofre-Sucre, Colombia - Néstor Jaime Aguirre; Jaime Alberto Palacio; Elkin Libardo Ríos (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
Profiles of water temperature, dissolved oxygen, pH, electrical conductivity and the salinity were measured in the swamp El Eneal municipality of San Onofre, Sucre, following a nictemeral design between May/2003 and April/2004. It was found that the system is completely mixed from the thermal point of view due to the action of the wind, in combination with the morphology and its location near the coastal line. It was also found that this coastal swamp is oligohalin, nevertheless most of the time the system can be considered as a limnetic system. During prolonged droughts, the salinity reached its maximum value of 3.4 ppm, which could become a limited factor for communities of strictly limnetics organisms.